2016
DOI: 10.1590/1678-4324-2016150650
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Hydroxyapatite Content in Soft Gelatin Affects Mesenchymal Stem Cell Differentiation

Abstract: Gelatin is a common material used in tissue engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A study by Kantawong et al showed that addition of nano-hydroxyapatite (HA) could enhance cell adhesion on a soft substrate and, maybe together with the releasing of Ca 2+ , induced a cell response to change gene expression and differentiation. Gelatin with 1.0 mg/mL supported neuronal gene expression in HMSCs, compared with pure gelatin and gelatin with 0.5 mg/mL of HA [53]. These studies supported that the influence of modulus on NSC differentiation that control stem cell fate would be possible for applications in reprogramming and cellular transdifferentiation.…”
Section: Biomimetic Biomaterials For Fibroblast Reprogrammingmentioning
confidence: 56%
See 1 more Smart Citation
“…A study by Kantawong et al showed that addition of nano-hydroxyapatite (HA) could enhance cell adhesion on a soft substrate and, maybe together with the releasing of Ca 2+ , induced a cell response to change gene expression and differentiation. Gelatin with 1.0 mg/mL supported neuronal gene expression in HMSCs, compared with pure gelatin and gelatin with 0.5 mg/mL of HA [53]. These studies supported that the influence of modulus on NSC differentiation that control stem cell fate would be possible for applications in reprogramming and cellular transdifferentiation.…”
Section: Biomimetic Biomaterials For Fibroblast Reprogrammingmentioning
confidence: 56%
“…Moreover, GA residuals can be harmful to the cultured cells. This problem was solved by soaking hydrogels in water before lyophilization to remove all GA residuals [52,53]. Various methods and principles about hydrogel crosslinking were provided by Hu et al [54].…”
Section: Biomimetic Biomaterials For Fibroblast Reprogrammingmentioning
confidence: 99%
“… 19 Furthermore, it was shown that the biomaterials from the study of Tanum et al 19 could induce a neural differentiation in the HMSCs. 20 The present study aimed to demonstrate that the gelatin-hydroxyapatite-pig brain biomaterials could induce the expression of the reprogramming factor Klf4 and nerve transcription factors, such as NFIa, NFIb, and SOX9 in fibroblasts. Thus, we hypothesized that biomaterials could be used effectively and economically as a tool to generate iNSCs from fibroblasts.…”
Section: Introductionmentioning
confidence: 96%
“…A previous study showed that photocurable hydrogel made from pure gelatin possessed ultrasoft property which induced neural differentiation in adipose derived stem cells (Kantawong et al, 2015). When hydroxyapatite was added to pure gelatin, it was found that the material could induce neural differentiation in hMSCs (Kantawong et al, 2016). If gelatin was applied on its own as the material of the scaffold, it would not be possible to obtain the kind of scaffold that could provide enough mechanical and physical properties for wound regeneration.…”
Section: Introductionmentioning
confidence: 99%